Geriatric Assessment of the Portuguese Population Aged 65 and Over Living in the Community: The PEN-3S Study - Madeira, T (2020)
Introduction: As populations live longer, they also aim to live better. A crucial step for this is to improve the understanding about older adults' physical and psychological health. Therefore, the aim of the present study was to characterise the Portuguese population over-65 regarding nutritional status, cognitive function, functional status, symptoms of depression, and loneliness, by sex and age groups. Material and methods: Cross-sectional study including a nationally representative sample of community-dwelling adults aged 65 and over. Trained interviewers collected data face-to-face on demographic and socioeconomic characteristics, health status, nutritional status, cognitive function, functional status for activities of daily living, symptoms of depression, and loneliness feelings. Complex sample procedures were used in the statistical analysis. Results: Overall, 1120 community-dwellers (49.0% women, 21.3% aged ≥ 85) participated in the study. The estimated prevalence of risk of malnutrition was 16.4% (95% confidence interval: 13.3 - 19.9), while 17.7% (95% confidence interval: 12.8 - 23.9) were cognitively impaired, and 28.5% (95% confidence interval: 23.7 - 33.8) presented limitations to perform daily living activities. Moreover, 23.5% (95% confidence interval: 19.7 - 27.7) presented symptoms of depression and 13.6% (95% confidence interval: 10.6 - 17.1) reported loneliness feelings. These conditions were more prevalent among women, and generally more frequent in the oldest individuals (≥ 85). Discussion: Risk of malnutrition, cognitive impairment, functional limitations, depression and loneliness were moderately frequent, which may justify screening and preventive actions at a community level. Conclusion: This study contributed to a national characterisation of the health of older adults, that may inform policies and interventions targeted at the needs of the Portuguese aging population.